Relasi Manusia dengan Lingkungan dalam Al-Qur'an Upaya Membangun Eco-Theology - Iswanto, Agus (SUHUF, 2013)
This writing tries to explore the relation between the humankind and the environment in Islam through the keywords in the QurÃ¢â‚¬â„¢an. It is begun by examining six perspectives concerning the relation between the humankind and the environment. Further, the writer explores the relation of the humankind and the environment in the QurÃ¢â‚¬â„¢an by using two concepts: the first is the goal of the creation of the universe and the goal of the creation of humankind. There are four concepts for building eco theology. They are: taskhÃ„Â«r,( the submission) Ã¢â‚¬Ëœabd,(servant)Ã‚Â  khalÃ„Â«fah (vicegerent) and amÃ„Ânah (trust).Therefore, to build the harmony of the eco-system based on religious understanding, the balance of the four concept mentioned above is needed.